Toxicological Evaluation of Copper Oxychloride on Carassius Auratus: Determining Lethal Concentrations and Behavioural Responses - Ullah, Naseer; Ali , Asad; Khan, Fawad Ali; Rahman, Hamid Ur; Ihteshamullah, Syed (International Journal of Agriculture Innovations and Cutting-Edge Research (HEC Recognised), 2025)
Pesticides are widely used in agriculture to control pests. Cobox (copper oxychloride) is a broad-spectrum organophosphate fungicide widely used against pests. The use of pesticides not only controls pests, but it is also very harmful to non-target organisms. The present study aimed to find out the lethal concentrations (LC) LC0, LC50 and LC100 for 24, 48, 72 & 96 hours and behavioural changes of copper oxychloride on wild goldfish (Carassius auratus) at District Swat. The fish samples were collected from the River Swat at different localities and acclimatized for three weeks in aquaria. The LC0 (safe lethal concentration) for 24, 48, 72 and 96 hours were 75 mg/l, 60 mg/l, 20 mg/l and 12 mg/l, respectively. The LC50 (sublethal concentration) for 24, 48, 72 and 96 hours were 125 mg/l, 95 mg/l, 60 mg/l and 50 mg/l, respectively. The LC100 (lethal concentration) values for 24, 48, 72 and 96 hours were 190 mg/l, 125 mg/l, 95 mg/l and 60 mg/l, respectively. The behavioural changes in exposed groups included irregular swimming, loss of body equilibrium, loss of scales, increased opercular movements, over secretion of mucus, altered feeding behaviours, jerky type of movements and coming towards the water surface. It is concluded that Cobox is lethal to Carassius auratus, and the use of safer pest control methods should be adopted.